Towards a greater engagement of universities in addressing climate change challenges - Walter Leal Filho and Sebastian Weissenberger and Johannes M. Lütz and Javier Sierra and Izabela Simon Rampasso and Ayyoob Sharifi and Rosley Anholon and Joao Henrique Paulinho Pires Eustachio and Marina Kovaleva (Scientific reports, 2023)
Many higher education institutions around the world are engaged in efforts to tackle climate change. This takes place by not only reducing their own carbon footprint but also by educating future leaders and contributing valuable research and expertise to the global effort to combat climate change. However, there is a need for studies that identify the nature of their engagement on the topic, and the extent to which they are contributing towards addressing the many problems associated with climate change. Against this background, this paper describes a study that consisted of a review of the literature and the use of case studies, which outline the importance of university engagement in climate change and describe its main features. The study identified the fact that even though climate change is a matter of great relevance to universities, its coverage in university programmes is not as wide as one could expect. Based on the findings, the paper also lists the challenges associated with the inclusion of climate change in university programmes. Finally, it describes some of the measures which may be deployed in order to maximise the contribution of higher education towards handling the challenges associated with a changing climate.
Keywords: Climate change; Environmental impact